Contact allergy to and allergic contact dermatitis from formaldehyde and formaldehyde releasers: A clinical review and update - Goossens, An; Aerts, Olivier (Contact dermatitis, 2022)
This review aims to provide a clinically useful update regarding the role of formaldehyde (FA) and its five main releasers (FRs) quaternium‐15, diazolidinyl urea, DMDM hydantoin, imidazolidinyl urea, and 2‐bromo‐2‐nitropropane‐1,3‐diol (bronopol) in contact allergy and allergic contact dermatitis. These ubiquitous preservatives are still often present, and sometimes undeclared, in cosmetics, pharmaceuticals, medical devices, household detergents, and chemical (industrial) products. In Europe, the use of free FA and quaternium‐15 in cosmetics is forbidden and contact allergy rates have been found to be stable to decreasing. However, FA/FRs still readily provoke localized (eg, facial/hand), airborne, and generalized dermatitis, and may also complicate atopic and stasis dermatitis, or result in nummular dermatitis. Seborrheic‐, rosacea‐ and impetigo‐like dermatitis have recently been reported. For a correct diagnosis, FA 2% aq. (0.60 mg/cm2) should be used, and particularly the FRs bronopol 0.5% pet. and diazolidinyl urea 2% pet. should be patch tested separately in a baseline series. If sensitization to FA occurs, both FA and FRs should preferably be avoided, except perhaps for bronopol in case it tests negatively. If a patient reacts to one or more FRs (such as bronopol or diazolidinyl/imidazolidinyl urea), but not to FA, then the specific FR(s) should be avoided.